2012
DOI: 10.1128/iai.00279-12
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Mucosa-Associated Invariant T Cells Have Unique Innate Functions in Bacterial Infection

Abstract: ABSTRACTMucosa-associated invariant T (MAIT) cells are a unique population of αβ T cells in mammals that reside preferentially in mucosal tissues and express an invariant Vα paired with limited Vβ T-cell receptor (TCR) chains. Furthermore, MAIT cell development is dependent upon the expression of the evolutionarily conserved major histocompatibility complex (MHC) class Ib molecule MR1. Usingin vitroassays, recent studies have shown that mouse and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
313
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(326 citation statements)
references
References 80 publications
11
313
2
Order By: Relevance
“…Activated peripheral MAIT cells produce large quantities of IFN-g and TNF-a but also possess a Th17-signature profile, because they release IL-17A after mitogen stimulation and express the Th17-associated transcription factor RORC and the Th17-related chemokine receptor CCR6 (16,17). The functional and developmental profile of MAIT cells, together with their preferential localization in the vascular bed of the gut and liver, indicate that MAIT cells may play a major role in controlling the dissemination of pathogens that could escape the gut mucosal barrier (19) or be implicated in liver pathological processes of different etiologies (20). However, the objective difficulties in obtaining samples from human parenchymal organs, particularly in nonpathological situations, have hampered the functional characterization of MAIT cells from the human liver.…”
mentioning
confidence: 99%
“…Activated peripheral MAIT cells produce large quantities of IFN-g and TNF-a but also possess a Th17-signature profile, because they release IL-17A after mitogen stimulation and express the Th17-associated transcription factor RORC and the Th17-related chemokine receptor CCR6 (16,17). The functional and developmental profile of MAIT cells, together with their preferential localization in the vascular bed of the gut and liver, indicate that MAIT cells may play a major role in controlling the dissemination of pathogens that could escape the gut mucosal barrier (19) or be implicated in liver pathological processes of different etiologies (20). However, the objective difficulties in obtaining samples from human parenchymal organs, particularly in nonpathological situations, have hampered the functional characterization of MAIT cells from the human liver.…”
mentioning
confidence: 99%
“…A recent study indicated that MAIT cells recognize riboflavin (vitamin B2) derivatives in an MHC class 1b-like related protein (MR1)-dependent manner (7). After Ag recognition, MAIT cells rapidly produce Th1/Th17 cytokines, such as IFN-g and IL-17, in an innate-like manner (6), and they contribute to protection against certain mycobacterial and enterobacterial infections (3,4,(8)(9)(10).…”
mentioning
confidence: 99%
“…Finally, the preferential localization of MAIT cells in the lining of mucosal surfaces and their protective role in several infections [8,9,13,14] …”
mentioning
confidence: 99%